Toxicological Effects of Silver-Modified Bentonite Nanocomposites on Microalgae: Impact on Cell Growth, Antioxidant Enzymes, and Gene Expression - Oumayma Ghariani; Jihen Elleuch; Anna Maria Ferretti; Stefano Econdi; Chiara Bisio; Philippe Michaud; Imen Fendri; Matteo Guidotti; Slim Abdelkafi (Nanomaterials)
The increasing use of nanostructured silver-containing inorganic materials raises concerns about their impact on aquatic organisms. This study assessed the toxicity of silver-modified bentonite composites on Chlamydomonas sp. Two materials were tested: silver-exchanged bentonite (Ben-Ag) and its reduced form (Ben-Ag (H2)).Microalgae were exposed to 0.5 IC50, 1.5 IC50, and 2 IC50. Ben-Ag showed higher toxicity than Ben-Ag (H2), which even promoted algal growth at low doses. Fluorescence microscopy revealed morphological shrinkage in treated cells. Increased phenol content, elevated malondialdehyde (MDA) levels, and altered antioxidant enzyme activities further confirmed Ben-Ag toxicity, along with reduced growth and photosynthetic pigments. Transcriptomic analysis revealed significant changes in gene expression under Ben-Ag exposure. Genes involved in photosynthesis (petB, psbL), caspase activity (casp), and carotenoid metabolism (Q2CHY) were down-regulated, indicating stress-induced damage. In contrast, genes encoding stress response enzymes (SOD, peroxidase), carbon metabolism enzymes (rbcL, PGQ1), and β-carotene biosynthesis (Q2BKT) were up-regulated, reflecting cellular defense mechanisms. Overall, the study highlights the high toxicity of Ben-Ag to Chlamydomonas sp., emphasizing the importance of evaluating environmental risks before using such materials in aquatic environments.